ANALISIS PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA YANG BERKEBUTUHAN KHUSUS - Mahardika, Muchammad Ardian; Munir, Muhammad Misbahul (STKIP Persada Khatulistiwa Sintang, 2024)
Education is provided for all groups, including children with special needs. However, the role of teachers for children with special needs is not easy, especially in increasing their learning motivation. This research aims to describe the role of teachers in increasing the learning motivation of students with special needs. The research was carried out using qualitative methods, with the research subjects are teachers at SD Al Islam, Pengkol, Jepara. Data was obtained through interviews. The research results show that teachers have a very important role as a motivator in providing motivation and will influence the child's growth and development.